Liver X Receptors (LXRs) in cancer-an Eagle’s view on molecular insights and therapeutic opportunities - Ramalingam, Prasanna Srinivasan; Elangovan, Sujatha; Mekala, Janaki Ramaiah; Arumugam, Sivakumar (Frontiers in Cell and Developmental Biology, 2024)
Cancer has become a serious health burden that results in high incidence and mortality rates every year, mainly due to various molecular alterations inside the cell. Liver X receptors (LXRs) dysregulation is one among them that plays a vital role in cholesterol metabolism, lipid metabolism & inflammation and also plays a crucial role in various diseases such as obesity, metabolic dysfunction-associated fatty liver disease (MAFLD), cardiovascular diseases, Type 2 diabetes, osteoporosis, and cancer. Studies report that the activation of LXRs inhibits cancer growth by inhibiting cellular proliferation, inducing apoptosis & autophagy, regulating cholesterol metabolism, various signalling pathways such as Wnt, & PI3K/AKT, modulating the expression levels of cell-cycle regulators, and promoting antitumor immunity inside the tumor microenvironment. In this review, we have discussed the role, structure, & functions of LXRs and also summarized their ligands along with their mechanism of action. In addition, the role of LXRs in various cancers, tumor immunity & tumor microenvironment (TME) along with the importance of precision medicine in LXR-targeted therapies has been discussed to emphasize the LXRs as potent targets for the development of novel cancer therapeutics.